2016
DOI: 10.1007/s00701-016-2718-3
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implants in the etiopathogenesis of glioblastoma–an interesting observation or independent finding?

Abstract: Various risk factors have been implicated in the pathogenesis of glioblastomas including ionizing radiation. Recent evidence has suggested a possible association between exposure to nonionizing radiofrequency electromagnetic fields (RF-EMF) generated from mobile phones and wireless devices to cause malignant transformation of the neuroglial cells, albeit this is widely debated. In this report, we discuss the development of glioblastoma in two geopolitically unrelated patients, an elderly male from the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…Contrary to the concerns raised by our recently published case report, 6 we did not find an increased risk of malignant glioma, meningioma, or schwannoma in our cohort of patients with cochlear implants. The RF-EMFs generated by a cochlear implant are thus unlikely to induce tumors.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to the concerns raised by our recently published case report, 6 we did not find an increased risk of malignant glioma, meningioma, or schwannoma in our cohort of patients with cochlear implants. The RF-EMFs generated by a cochlear implant are thus unlikely to induce tumors.…”
Section: Discussioncontrasting
confidence: 99%
“…We cannot rule out that a more highly powered study would find weak associations between exposure and tumor incidence. Still, the only patient with a glioblastoma among the cochlear implant patients in Sweden was our one Swedish index case in the case report (the other was from the USA) 6 and the absence of additional patients is indicative of low risk. Various risk factors have been associated with glioma, 8 but cochlear implants were only suggested in our previous report of two cases of glioblastoma after long-term cochlear implantation.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The authors speculate that electric fields associated with the treatment could have caused the tumour. The authors also mention a case report describing the development of glioblastoma in two patients who had cochlear implants, where it was suggested that the tumours might be attributed to the electromagnetic fields from the implants [5]. Both of these are interesting observations, although alternative explanations for the occurrence of the tumours in these patients may be at least as, or even more, plausible.…”
mentioning
confidence: 91%